The endocannabinoid system as a therapeutic target in intestinal fibrosis - Misztal, Zofia; Kaśniewska-Kosińska, Alicja; Wołyniak, Maria; Małecka-Wojciesko, Ewa; Fabisiak, Adam (Frontiers in Pharmacology, 2025)
Intestinal fibrosis is a common and serious complication of inflammatory bowel diseases, often leading to strictures that require endoscopic or surgical intervention. Despite advances in anti-inflammatory therapies, effective antifibrotic treatments is currently not available. Therefore, new treatment methods for intestinal fibrosis are sought with the endocannabinoid system (ECS) as a potential therapeutic target. Cannabinoid receptors 1 and 2 (CB1/2) are classic receptors of the ES involved in the modulation of intestinal inflammation and permeability of the mucosal barrier. Experimental evidence from liver and lung models suggests that CB1 receptor activation promotes fibrosis through enhancement of the TGF-β/Smad pathway, interaction with the renin-angiotensin system, and upregulation of profibrotic markers, such as collagen and α-SMA. In contrast, CB2 receptor signaling appears to exert protective effects by limiting inflammation, fibroblast activation, and extracellular matrix deposition. Recent findings also suggest cross-talk between cannabinoid signaling and platelet-derived growth factor pathways, which are key drivers of myofibroblast proliferation and fibrogenesis. Although these mechanisms are well-established in hepatic, pulmonary and skin fibrosis, data from small and large intestine is scarce. However, direct evidence in intestinal fibrosis is scarce, representing a major knowledge gap. Elucidating ECS mechanisms in the alimentary tract could enable targeted antifibrotic strategies, complement current therapies, and reduce progression to fibrostenotic disease.